Влијанието на урсодеоксихолната киселина на функционална реставрација на црниот дроб кај пациенти со опструктивна жолтица по ендоскопски третман - Фекај, Енвер (Медицински факултет, УКИМ, Скопје, 2017)
Background: The most common causes of obstructive jaundice are choledocholithiasis, strictures of the biliary tract, cholangiocarcinoma, carcinoma of pancreas, pancreatitis, parasites and primary sclerosing cholangitis. When mechanical biliary obstruction is diagnosed, surgical, endoscopic or radiologic intervention is usually recommended. The aim of this study was evaluation of the effect of UDCA in liver functional restoration of patients with obstructive jaundice in the early period after endoscopic intervention. Specific aims consisted on the evaluation of the effect of UDCA in relation to etiology of obstructive jaundice, to gender, and to age of patients. Methods: In this prospective, randomized, open-labeled, and controlled study, 62 patients were enrolled. After diagnosis, eligible patients with obstructive jaundice who met inclusion criteria were randomly divided in the investigation group (n= 31) in which has been administered UDCA, and in the control group (n= 31). UDCA administration started twenty-four hours after endoscopic treatment. It was administered at 750 mg/day, divided into three daily doses and lasted fourteen days. Serum-testing in patients with obstructive jaundice included determination of bilirubin (total and direct fractions), alanine transaminase (ALT), aspartate transaminase (AST), gama-glutamil transpeptidase (GGT), alkaline phosphatase (ALP), albumin, neutrophil/ lymphocyte ratio (N/L ratio), urea, glucose, and creatinine. These parameters were determined one day prior endoscopic intervention, and on the fifth, tenth, and fifteenth days after endoscopic intervention. The primary outcome measure in this study was bilirubin, alkaline phosphatase, and GGT serum levels decreasing rate. The secondary outcome was assessment liver functional parameters in which, treatment with UDCA, have had greater impact. Results: The difference of the average values of total and direct bilirubin, between the groups, was statistically significant at day 0 (p<0.05), but at other evaluation days was not statistically significant, while the difference of the average values of ALT, AST, GGT, ALP, N/L ratio, urea, glucose, and creatinine, between the groups, was not statistically significant (p>0.05). The difference of the average values of albumin, between the groups, was statistically significant at the days 5, 10, and 15 (p<0.05). The decrease rate of total bilirubin, direct bilirubin, GGT, and N/L ratio, between the day 15 compared to day 0, was higher in the IG than in the CG (total bilirubin; 72.6 % vs 67.6 %, direct bilirubin; 78.1 % vs 71 %, GGT; 71.5 % vs 63.4 %, and N/L ratio; 29 % vs 17 %, respectively), while the decrease rate of ALT, AST, and ALP was higher in the CG than in the IG (ALT; 69.8 % vs 67.7 %, AST; 62.2 % vs 59.5 %, ALP; 50.8 % vs 47.9 %, respectively). The albumin level, in the IG, between the day 15 compared to day 0, was decreased 3.9%, while in the CG the albumin level was increased 5.4%. The levels of urea and creatinine were increased in both groups, but the difference of the average values of these parameters, between the groups, was not statistically significant. The increase rate of urea was higher in the CG than in the IG (22.6 % vs 8.1 %, respectively), while creatinine was higher in the IG than in the CG (14.7 % vs 13 %, respectively).The difference between the average values of all parameters according gender (female vs male) was not statistically significant in the IG (p>0.05). Gender had no significant impact on the values of total and direct bilirubin at all evaluation days in the IG, but had in the CG (p= 0.022365; p= 0.038479, respectively). Also, gender had no significant impact on the values of ALT, AST, GGT, ALP, albumin, N/L ratio, urea, glucose, and creatinine in both groups. On the other hand, etiology had a significant impact on the values of total bilirubin, direct bilirubin, ALP, and N/L ratio in the two groups (total bilirubin: p= 0.003774; p= 0.000533, direct bilirubin: p= 0.005922; p= 0.000022, ALP: p= 0.006942; p= 0.012625, N/L ratio: p= 0.014420; p= 0.000331, respectively). Etiology had a significant impact on the values of AST in the IG (p= 0.004172), but had no in the CG, while had no impact on the values of ALT, GGT, albumin, and creatinine in the groups. Also, etiology had no significant impact on the value of urea in both groups, and had no impact on the glucose in the IG, but had in the CG (p= 0.044487). Patient age had no impact on the values of total bilirubin at all evaluation days in the IG, but had in the CG (p= 0.008696). Age had no impact on the values of direct bilirubin, ALT, AST, GGT, ALP, and glucose in the groups. Also, age had no significant impact on albumin, urea, and creatinine levels and N/L ratio in the IG, but had in the CG (p= 0.010772; p= 0.003102; p= 0.023777; p= 0.001387, respectively). Conclusions: UDCA has accelerated reducing the level of total bilirubin, direct bilirubin, GGT, and neutrophil/lymphocyte ratio, but did not decrease the level of ALT, AST, and alkaline phosphatase, and did not induce increasing of albumin level. UDCA had greater impact on GGT than in other functional liver parameters. The effect of UDCA did not depend on the gender and the age of patients, but did depend on the etiology of obstructive jaundice. It was more effective in patients with choledocholithiasis than in patients with malign stenosis of biliary tree.
The influence of ursodeoxycholic acid in liver functional restoration in patients with obstructive jaundice after endoscopic treatment
Докторска дисертација одбранета во 2017 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Ники Матвеева.
Keywords: obstructive jaundice, ursodeoxycholic acid, treatment with UDCA